Smart Money for Smart Students: Pelatihan Literasi Keuangan melalui Pengelolaan Uang Jajan dan Pembiasaan Menabung bagi Siswa SMPN 3 Jati Agung - Febrianti, Werry; Fauzi, Rifky; Nasution, Achmad Suryadi; Noor, Dear Michiko Mutiara; Mardianto, Lutfi; Mustika, Mira; Rizka, Nela (Jurnal SOLMA, 2026)
Background: Financial literacy is an essential skill for young people; however, national reports indicate that Indonesian adolescents' financial literacy remains low, particularly in managing their daily allowance and controlling expenditures. This program aims to enhance basic financial literacy by training in pocket money management and developing regular saving habits. Methods: The community service activity was conducted over two visits. The first visit focused on training students to save and manage their allowance, accompanied by the distribution of character-themed piggy banks and financial logbooks. During the second visit, the team conducted a 30-day savings evaluation and reviewed students’ allowance management recorded in their logbooks. Results: The results show improved students’ understanding, as reflected in higher post-test scores. Furthermore, the one-month saving trends also showed increases in students’ balances, with varying patterns. Conclusions: These findings indicate the effectiveness of character piggy banks and logbook-based allowance management in fostering consistent saving habits among students.